1989
DOI: 10.1111/j.1365-2796.1989.tb01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of n‐3 fatty acids on blood lipids in normal subjects

Abstract: Influence of n-3 fatty acids on blood lipids in normal subjects. Journal oflnternal Medicine 1989: 225. Suppl. 1 : 99-104.The effects of consuming oils providing alpha-linolenic (ALA). eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids were studied in healthy volunteers. A blunted increase in plasma triglyceride was observed in subjects given a test meal containing fish oil compared with olive oil: cholesterol concentrations were not increased: increases in EPA and DHA were seen in all lipid fractions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 12 publications
3
22
1
Order By: Relevance
“…Moderate intakes of EPA and DHA, either as fish oil or ethyl esters, increase HDLz-cholesterol but high intakes decrease HDL-cholesterol, as seen with very high intakes of linoleic acid (Harris, 1989;Sanders et al 1989). This is accompanied by a decrease in both cholesterol transfer protein and lecithin-cholesterol acyltransferase (EC 2.3.1.43) activities (Abbey et al 1990) and these changes might explain the increase in HDL2:HDL3.…”
Section: Blood Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate intakes of EPA and DHA, either as fish oil or ethyl esters, increase HDLz-cholesterol but high intakes decrease HDL-cholesterol, as seen with very high intakes of linoleic acid (Harris, 1989;Sanders et al 1989). This is accompanied by a decrease in both cholesterol transfer protein and lecithin-cholesterol acyltransferase (EC 2.3.1.43) activities (Abbey et al 1990) and these changes might explain the increase in HDL2:HDL3.…”
Section: Blood Lipidsmentioning
confidence: 99%
“…Both EPA and DHA, but not a-linolenic acid, markedly lower plasma triacylglycerols and VLDL concentrations (Harris, 1989;Sanders et al 1989). Total or LDL-cholesterol concentrations are not usually influenced by moderate intakes (about 3 g n-3 fatty aciddday) of fish oil rich in EPA and DHA.…”
Section: Blood Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has demonstrated that ALNA and long-chain omega-3 PUFA supplementation have equivalent effects on haemostatic factors [31], however other studies have failed to observe significant effects of dietary ALNA on haemostatic variables [61,68]. In addition, unlike EPA and DHA, ALNA supplementation has no effect on plasma TAG concentrations [31,100] except at very high levels of dietary intake. Nevertheless there is some data to support modulatory effects of ALNA on eicosanoids, since ALNA has been shown to reduce blood pressure in hypertensives [105] and some data is available to suggest that ALNA can inhibit lymphocyte proliferation in animals [14] and in healthy adults [57,58] and more recently has been shown to suppress the production of TNF and IL-1 in subjects fed ALNA enriched diets [15].…”
Section: Approaches To Increasing Omega-3 Pufa Intakementioning
confidence: 99%
“…It has been demonstrated that both ALA and long-chain n-3 PUFA supplementation have equivalent effects on haemostatic factors (Freese & Mutanen, 1997). However, unlike EPA and DHA, ALA supplementation has no effect on plasma TAG concentrations (Sanders et al 1989;Freese & Mutanen, 1997). There are also differences between ALA and the long-chain n-3 PUFA in terms of disease outcome.…”
Section: Defining Optimal Levels Of N-3 Polyunsaturated Fatty Acid Inmentioning
confidence: 99%